2020
DOI: 10.1002/marc.202000275
|View full text |Cite
|
Sign up to set email alerts
|

Interpenetrating Network of Alginate–Human Adipose Extracellular Matrix Hydrogel for Islet Cells Encapsulation

Abstract: Transplantation of microencapsulated islet cells holds great potential for the treatment of type 1 diabetes mellitus. However, its clinical translation is hampered by the peri‐transplantation loss of islet viability and functionality in the microcapsules. In this work, a novel islet cells biomimetic microencapsulant material that is based on the interpenetrating networks of alginate and extracellular matrix (ECM) hydrogel composite (AEC) is presented. The ECM component is derived from human lipoaspirate. In si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 54 publications
(53 reference statements)
1
15
0
Order By: Relevance
“…Wang et al show that MIN6 β-cells could exhibit larger proliferation rate and higher glucose sensitivity with insulin secretion when human adipose ECM was incorporated, suggesting the importance of cell–matrix interaction. 19 Hence, hydrogels are excellent platforms for artificial functional islet construction, which could dynamically and precisely control glucose balance in vivo and circumvent the drawbacks of long-term insulin injection.…”
Section: In Vitro and In Vivo Potential Applications Of Hydrogelmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al show that MIN6 β-cells could exhibit larger proliferation rate and higher glucose sensitivity with insulin secretion when human adipose ECM was incorporated, suggesting the importance of cell–matrix interaction. 19 Hence, hydrogels are excellent platforms for artificial functional islet construction, which could dynamically and precisely control glucose balance in vivo and circumvent the drawbacks of long-term insulin injection.…”
Section: In Vitro and In Vivo Potential Applications Of Hydrogelmentioning
confidence: 99%
“…The interaction between cell and hydrogel is complex and dynamic, which exerts significant impacts on tissue physiological (e.g., cell spreading, 14 proliferation, 15 migration, 16 stemness, 17 differentiation, 18 etc.) and pathological processes, such as cell apoptosis, 19 fibrosis, 20 immunological rejection, 21 etc. Regarding this, a comprehensive and deep understanding of cell–hydrogel interaction especially at the molecular level is of great importance, which is helpful for guiding the rational design of hydrogels and facilitating their clinic translation in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In recent work, researchers have investigated strategies to improve the ability of this polymer to mimic a natural ECM matrix. In one such paper, researchers combined human adipose tissue-derived ECM hydrogel with ALG matrix to form hybrid interpenetrating network microparticles for encapsulation of islet cells [ 16 ].
Fig.
…”
Section: Mechanics Of Microencapsulationmentioning
confidence: 99%
“…In another study reported by Wang et al, novel thermosensitive interpenetrating networks (IPN) of alginate and human adipose tissue-derived ECM were fabricated as a biomimetic encapsulate environment for islets delivery (J. K. Wang J. K. et al, 2020 ). For encapsulation, islets were added to an alginate solution, then the system was crosslinked through ionic gelation, and finally, the microencapsulated structure was added to the ECM-derived hydrogel ( Figure 1 ).…”
Section: Hydrogel-based Encapsulation Devicesmentioning
confidence: 99%
“… Schematic illustrating fabrication steps alginate microcapsules containing human adipose tissue-derived ECM and microencapsulation of pancreatic islets (J. K. Wang J. K. et al, 2020 ). …”
Section: Hydrogel-based Encapsulation Devicesmentioning
confidence: 99%